Consistency Tests of Alternative Measures of Comparative Advantage - Ballance, Robert H.; Forstner, Helmut; Murray, Tracy (The Review of Economics and Statistics, 1987)
The commodity pattern of comparative advantage across countries is a central concept in international trade theory. Since the concept is based upon autarkic prices which are not observable in post-trade equilibria, its use in empirical research is most difficult. The literature reports numerous alternative indices that purport to comparative advantage. This paper examines the extent to which various measures are consistent using a large sample of trade flows. The results have important implication for judging empirical studies based upon particular choices of a measure for comparative advantage.